Emotional Intelligence As The Foundation For Open Communication Between Parents And Children In The Village of Karangampel - Ayu Salsabillah Putri; Khaerudin Imawan; Welly Wihayati (ann4publisher@gmail.com, 2026)
Background. This research is motivated by the urgency of emotional intelligence as a basis for open communication within the family, especially in coastal communities in Karangampel Village, Indramayu Regency, which tend to adhere to traditional parenting patterns. Aims. This study aimed to identify how the dimensions of parental emotional intelligence (self-awareness, empathy, social skills) affect the child's willingness to communicate openly. Methods. The study used a qualitative case study design, involving three family units (parents and adolescents aged 14–18 years) selected through purposive sampling. Data collection was conducted through in-depth interviews, participatory observations, and documentation, and the data were analyzed using the interactive analysis model of Miles, Huberman, & Saldaña. Result. The results of the study show that parental self-awareness is manifested in taking post-conflict pauses, but without explicit communication, children interpret it as avoidance; empathy through past reflection helps parents understand the child's behavior as a normal part of development; As well as social skills in the form of physical touch and soft tone encourage children's courage to open up. Conclusion. This study concludes that parents' emotional intelligence plays an important role in opening communication, with practical implications for strengthening PUSPAGA services in coastal areas.